Estudo da iteração geótipo-ambiente para características produtivas em bovios Gir leiteiro - Luciana Salles de Freitas (2012)
The genetic evaluations in Brazil for milk production and other traits do not take in account the genotype by environment interaction in the model. Aiming to evaluate the genotype by environment interaction (GxE) for milk production, fat and protein content in Gyr breed in Brazil, this study was undertaken to study several methodologies used to identify this interaction (GxE) considering different environment conditions. The study of phenotype in different herds suggested the existence of GxE interaction for milk production and indicated the need of further studies to consider levels of average milk production of herd with different environments. Multivariate analysis was performed to estimate the genetic correlation between the same trait under different environment conditions (average levels of herd milk production and different biomes).The results of these studies showed the correlations varied from low to moderate (varied from .39 to .53 for levels of milk production and .58 for different biomes) suggesting a significant effect of GxE for milk production. Random regression models using reaction norms were used to identify the environment sensitivity for milk production, fat and protein of animals to changes in environment conditions. The reaction norms were efficient in identifying this sensitivity, expressed either by an increase in the dispersion of genetic values or in the changes of genetic values ranking. The results of this study indicated that animals showing higher genetic values in one environment do not maintain the same superiority in other environments, suggesting the need of including the GxE in genetic evaluations of milk production in Gyr breed in Brazil